Report of the Secretary-General on the Work of the Organization 2023 - United Nations (United Nations, 2023)
The Report of the Secretary-General on the Work of the Organization (A/78/1) is issued in response to Article 98 of the UN Charter and highlights how the UN Secretariat translates resources into impact. The Report covers nine sections: (i) promotion of sustained economic growth and sustainable development; (ii) maintenance of international peace and security; (iii) development in Africa; (iv) promotion of human rights; (v) effective coordination of humanitarian assistance; (vi) promotion of justice and international law; (vii) disarmament; (viii) drug control, crime prevention and combating international terrorism; and (ix) effective functioning of the Organization. The e-book for this publication has been converted into an accessible format for the visually impaired and people with print reading disabilities. It is fully compatible with leading screen-reader technologies such as JAWS and NVDA.